Croton membranaceus Improves Some Biomarkers of Cardiovascular Disease and Diabetes in Genetic Animal Models - George Awuku Asare; Samuel Adjei; Daniel Afriyie; Akua Bempomaa Appiah-Danquah; Jonas Asia; Bernice Asiedu; Sheila Santa; Derek Doku (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Cardiovascular disease (CVD) accounts for 17.3 million deaths per year globally. In Ghana, CVD accounts for 22.2% of deaths. Croton membranaceus (CM) Mull. Arg. (Euphorbiaceae), a medicinal plant in Ghana is mainly used traditionally for the treatment of benign prostatic hyperplasia and measles. However, some hypoglycaemic and hypotensive effects have recently been reported but not scientifically examined. Aim: The study aimed at establishing whether Croton membranaceus (CM) used for prostatitis had any effect on CVD markers. Materials and Methods: In experiment 1, lipid profile changes were determined. Twenty four male Spontaneously Hypertensive Rats (SHR) were divided into 4 groups. Low (LD), intermediate (ID) and high dose (HD) groups received 25, 50 and 100 mg/kg b.wt. CM aqueous root extracts (CMARE) for 60 days, respectively, the controls received distilled water. In experiment 2, blood glucose levels (BGL) were determined. 21 db/db mice were divided into 3 groups of 7 mice each alongside db/+ mice (7) (negative control). Groups 1 and 2 received 250 mg/kg b.wt CMARE and metformin, respectively. Group 3 (positive control) and db/+ mice (negative control) received distilled water. Mice were monitored for 15 hours. Data collected were analysed using SPSS version 20. Results: Hypotriglyceridaemic effect was observed (p=0.005). High Density Lipoprotein cholesterol (HDL) and Low Density Lipoprotein cholesterol (LDL) showed significant increases (p=0.013) and decreases (p=0.003), respectively. A significant CRP reduction was observed for ID and HD groups (p = 0.010, p = 0.011, respectively). BGL was reduced in Metformin and Croton groups (p=0.000; p= 0.006, respectively) after 3 hours. Conclusion: In conclusion, CMARE has positive effects on some CVD biomarkers and a hypoglycaemic effect.